Children's Hospital Management in the COVID-19 Era: The Reorganization of a Tertiary Care Pediatric Emergency Department in Northern Italy - Donà, Daniele; Masiero, Susanna; Costenaro, Paola; Todeschini Premuda, Marco; Rossin, Sara; Perilongo, Giorgio; Saieva, Anna M.; Giaquinto, Carlo; Da Dalt, Liviana (Frontiers in Pediatrics, 2020)
In the Veneto Region, an exponential spread of patients affected by 2019 novel Coronavirus disease (COVID-19) has been observed after February 21st. Since then, we have been evaluating children suspected or confirmed for SARS-CoV-2 infection. A protocol for pediatric hospital reorganization and children management has been developed, since the beginning of the epidemic. A pre-triage area has been created at the immediate entrance of the pediatric emergency room, for all uncritical pediatric patients. According to the epidemiologic and clinical risk factors, all children/adolescents have been addressing to one of the four different pathways created. The strict application of this protocol has been leading to quickly identification, isolation and management of all positive children, preventing SARS-CoV-2 intrahospital spread.